Thermoelectric Generator Demonstration On Stove As Alternative Energy - Sudarmanto Jayanegara; Muhammad Wiranda; Kamaluddin (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
Thermoelectric generators are power plants that utilize the Seebeck effect, a phenomenon that produces electric current when there is a temperature difference in a conductor or semiconductor. In practice, thermoelectric generators are often used to utilize waste heat from various systems. One significant heat source is a stove, which can produce temperatures up to 80ºC. By utilizing a thermoelectric generator, the heat accumulated on the stove wall can be converted into electrical energy. To support this conversion, an effective cooling system is needed so that the temperature difference between the two sides of the thermoelectric module is maintained. This study aims to explore the potential of electrical energy generated by a thermoelectric generator (TEG) module as an alternative energy source through heat from the stove wall with variations in flame settings. The cooling system used consists of an aluminum heat sink and a fan, which works to maintain the temperature difference on the cold side of the thermoelectric at around 12ºC. The test results show that the performance of the thermoelectric generator has quite promising potential as an alternative energy source. This can be seen from the increase in efficiency obtained from each flame variation. In large flames, the maximum measured efficiency value reaches 0.76%, while in small flames it reaches 0.47%. Therefore, the application of the Seebeck effect principle shows very good potential for the development of alternative energy in the future.